An analysis of direct and indirect costs in Hidradenitis Suppurativa - Claudine Howard‐James; Anne‐Marie Tobin (Wiley, 2024)
Abstract Background Hidradenitis Suppurativa (HS) is a chronic inflammatory skin condition with recurrent nodules and abscesses that culminate in purulent discharge and scarring. It has significant physical, psychological and financial impact. Objectives This study plans to analyse patient costs associated with HS. Direct costs include prescription items. Indirect or out‐of‐pocket costs include dressings, analgesia, and healthcare‐related travel costs. This study will also assess disease impact on quality‐of‐life (QOL). Methods Patients with HS diagnosis attending dermatology OPD at our public tertiary centre were invited to participate. Ethical approval was secured, and informed consent was obtained. Participants completed an anonymous survey which was analysed to identify costs associated with HS as well as demographics and QOL impact. Results A total of 25 patients completed the survey; median age was 29% and 80% were female. Median time from HS onset to diagnosis was 2 years, with 24% waiting >10 years to be diagnosed. In the past 3 months, 20% spent >€200 in both categories; prescription and non‐prescription items. In the non‐prescription category, 36% of patients reported expenditure >€100 in the past 3 months. Dressings were the most common out‐of‐pocket expense (in 15/25 patients), followed by analgesia and protective clothing. Attendance at medical appointments cost 24% of patients €50-€200. Four participants reported difficulty accessing HS treatments due to associated costs. Mean number of absence days from work/education as result of HS was 8.7 in the past 3 months. Two patients reported being on disability allowance, and two on unemployment benefit as result of their skin disorder. In the QOL question; 96% reported disease impact on QOL, and 11 participants reported that it affected their life 'very much'. Conclusions HS is a chronic inflammatory skin condition with significant financial burden alongside the well‐analysed biopsychosocial disease impact. Financial burden can be divided into direct prescription costs and indirect costs such as non‐prescription items, protective clothing and travel costs which we have explored in this study. Further research is needed in this area to identify and optimise both the financial and QOL implications of HS in acute flares and chronic disease management.